Parity-Time coupled microresonators: Kramers-Kronig limitation - Phang, Sendy; Vukovic, Ana; Creagh, Stephen C.; Sewell, Phillip; Gradoni, Gabriele; Benson, Trevor M.
In this talk, we use a KKE argument to show that the presence of dispersion alters the eigen-frequencies of coupled PT coupled microresonators, so that their eigen-frequencies are no longer complex conjugates after the EP.